Caries in temporary dentition in children of 6 years, parish Machángara, Cuenca 2016 - García López, Jorge (2021)
Objetive: To determine the prevalence of caries in schoolchildren of 6 years of age in the Machángara parish of the Cuenca city in 2016. Materials and Methods: A cross-sectional descriptive study was carried out on epidemiological aspects, the sample consisted of 104 patients of 6 years old, of which 58% corresponded to females and 42% to males. For the detection of the disease the operators were calibrated and standardized in universal criteria of the World Health Organization on the use of epidemiological indexes applied to the primary dentition. Results: The results obtained showed that the prevalence of caries in the 6-year-old students of the Machángara parish is 87.50%. It was also found that the distribution of the disease according to sex is higher in the female sex with a percentage 59%, compared to the male sex that has a percentage of 41%. Conclusions: Dental caries evidently reaches high prevalence values in the study population, which is why it is suggested to initiate standardized preventive programs and to take appropriate therapeutic measures to avoid exacerbating the health status of the patients examined.